Premature Mortality From Noncommunicable Diseases in the Federated States of Micronesia, 2003-2012. (April 2017) - Gopalani, Sameer Vali; Samo, Marcus; Soaz, Siocy; David, Wincener J.; Mori, Scott; Luther, X-ner; Carter, Karen L.
This study was conducted to assess status, and understand burden, of premature and leading causes of deaths from noncommunicable diseases (NCDs) in the Federated States of Micronesia (FSM). From 2003 to 2012, ICD-10 coded mortality data from the national Health Information System were analyzed. Proportional mortality was calculated and a ranking list of the leading causes of premature death was produced. Of the 2349 premature deaths reported, 1970 (83.9%) were due to NCDs, and 1680 (71.5%) were from 4 main NCD groups—cardiovascular diseases, cancer, diabetes, and chronic respiratory diseases. Diabetes (19.5%), ischemic heart diseases (13.2%), and cerebrovascular diseases (7.1%) were the leading causes of premature deaths. The findings indicate that the burden of premature NCD deaths in FSM is higher than global levels, and existing efforts need to be strengthened to alter their course.